Stochastic Duel with Several Types of Weapons - Bhashyam, N. (Defence Science Journal, 2014)
This paper attempts to study a 'Stochastic Duel' model wherein each of the contestants has got more than one type of weapons. The ultimate probability of win for each of them is evaluated and the results for a few particular cases are given.